Living Voices: The Oral History Interview as Dialogue and Experience. (1st August 2018) - Portelli, Alessandro
Abstract: Based on the experience of field research in oral history, this article describes the oral history interview as an exchange of gazes and a cocreated narrative between subjects—the interviewer and the interviewee—who are both observer and observed and speak to each other across the line of their significant otherness. The interviewee is both a tool for historical research and the opening of a narrative space for the subjectivity of the interviewee, which becomes in turn a significant historical fact.